Functional traits predict drought performance and distribution of Mediterranean woody species - Lopez-Iglesias, Bárbara; Villar, Rafael; Poorter, Lourens (Acta Oecologica, 2014)
Water availability is one of the key environmental factors that affect plant establishment and distribution. In many regions water availability will decline with climate change, exposing small seedlings to a greater likelihood of drought. In this study, 17 leaves, stem, root, and whole-plant traits of ten woody Mediterranean species were measured under favourable growing conditions and seedling drought survival was evaluated during a simulated dry-down episode. The aims of this study were: i) to assess drought survival of different species, ii) to analyse which functional traits predict drought survival time, and iii) to explain species distribution in the field, based on species drought survival and drought strategies. Drought survival time varied ten-fold across species, from 19 to 192 days. Across species, drought survival was positively related to the rooting depth per leaf area, i.e., the ability to acquire water from deeper soil layers while reducing transpiring leaf area. Drought survival time was negatively related to species ability to grow quickly, as indicated by high relative growth and net assimilation rates. Drought survival also explained species distribution in the field. It was found that species were sorted along a continuum, ranging between two contrasting species functional extremes based on functional traits and drought performance. One extreme consisted of acquisitive fast-growing deciduous species, with thin, soft metabolically active leaves, with high resource use and vulnerability to drought. The opposite extreme consisted of conservative slow-growing evergreen species with sclerophyllous leaves, deep roots, a low transpiring area, and low water use, resulting in high drought survival and drought tolerance. The results show that these drought strategies shape species distribution in this Mediterranean area.
Keywords: Drought; Functional groups; functional traits; mediterranean species; RGR; Rooting depth

SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Quero, José Luis; Villar, Rafael; Marañón, Teodoro; Zamora, Regino; Poorter, Lourens (American Journal of Botany 94(11):, 2007)
Three hypotheses have been proposed to explain the functional relationship between seed mass and seedling performance: the reserve effect (larger seeds retain a larger proportion of reserves after germinating), the metabolic effect (seedlings from larger seeds have slower relative growth rates), and the seedling-size effect (larger seeds produce larger seedlings). We tested these hypotheses by growing four Mediterranean Quercus species under different light conditions (3, 27, and 100% of available radiation). We found evidence for two of the three hypotheses, but none of the four species complied with all three hypotheses at the same time. The reserve effect was not found in any species, the metabolic effect was found in three species (Q. ilex, Q. pyrenaica, and Q. suber), and the seedling-size effect in all species. Light availability significantly affected the relationships between seed size and seedling traits. For Q. ilex and Q. canariensis, a seedling-size effect was found under all three light conditions, but only under the lowest light (3%) for Q. suber and Q. pyrenaica. In all species, the correlation between seed mass and seedling mass increased with a decrease in light, suggesting that seedlings growing in low light depend more upon their seed reserves. A causal model integrates the three hypotheses, suggesting that larger seeds generally produced larger seedlings.
From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )
Keywords: acornmass; Fagaceae; light availability; mediterranean oaks; Quercus; RGR; Seed size; seed–seedling relationships

SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Quero, José Luis; Villar, Rafael; Marañón, Teodoro; Zamora, Regino; Poorter, Lourens (American Journal of Botany 94(11):, 2007)
Three hypotheses have been proposed to explain the functional relationship between seed mass and seedling performance: the reserve effect (larger seeds retain a larger proportion of reserves after germinating), the metabolic effect (seedlings from larger seeds have slower relative growth rates), and the seedling-size effect (larger seeds produce larger seedlings). We tested these hypotheses by growing four Mediterranean Quercus species under different light conditions (3, 27, and 100% of available radiation). We found evidence for two of the three hypotheses, but none of the four species complied with all three hypotheses at the same time. The reserve effect was not found in any species, the metabolic effect was found in three species (Q. ilex, Q. pyrenaica, and Q. suber), and the seedling-size effect in all species. Light availability significantly affected the relationships between seed size and seedling traits. For Q. ilex and Q. canariensis, a seedling-size effect was found under all three light conditions, but only under the lowest light (3%) for Q. suber and Q. pyrenaica. In all species, the correlation between seed mass and seedling mass increased with a decrease in light, suggesting that seedlings growing in low light depend more upon their seed reserves. A causal model integrates the three hypotheses, suggesting that larger seeds generally produced larger seedlings.
From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )
Keywords: acornmass; Fagaceae; light availability; mediterranean oaks; Quercus; RGR; Seed size; seed–seedling relationships